Top 10 scariest animals - Maloney, Brenna (New York : Scholastic Inc., 2025)
"There are so many scary animals! Some of them are fierce predators. Some have giant fangs or teeth. Some sting. Some even spit venom. Learn all about the scary amphibians, birds, insects, mammals, and reptiles in our wild world. Count down from 10 to 1 and discover which one is the absolute scariest!"--
Ages 5-7
Grades K-1